1996
DOI: 10.1097/00003246-199611000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the humidity and temperature of inspired gas and the function of the airway mucosa

Abstract: A model for the relationship between airway mucosal dysfunction and the combination of the humidity of inspired gas and the duration over which the airway mucosa is exposed to that humidity is proposed. This model suggests that there is an optimal temperature and humidity above which, and below which, there is impaired mucosal function. This optimal level of temperature and humidity is core temperature and 100% relative humidity. However, existing data are only sufficient to test this model for gas conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
318
0
21

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(356 citation statements)
references
References 52 publications
6
318
0
21
Order By: Relevance
“…Other authors reported that low levels of humidification during a long period of NIV, i.e., 12 and 24 hours, was associated with less comfort and higher oral dryness feeling (28). However, whether heating and humidification of inspired gas may prevent thick secretions, potential dysfunction of mucociliary clearance, atelectasis facilitation and clinical impact is currently unproven (29).…”
Section: Comfort and Humidificationmentioning
confidence: 99%
“…Other authors reported that low levels of humidification during a long period of NIV, i.e., 12 and 24 hours, was associated with less comfort and higher oral dryness feeling (28). However, whether heating and humidification of inspired gas may prevent thick secretions, potential dysfunction of mucociliary clearance, atelectasis facilitation and clinical impact is currently unproven (29).…”
Section: Comfort and Humidificationmentioning
confidence: 99%
“…The system conditions the inspired gas to 37°C and 44 mg H 2 O/L, which is considered thermodynamically neutral to the airway, 3 preserving the function of the ciliated mucosa. 4 Recent work described complications associated with unhumidified high-flow face mask (HFFM) oxygen therapy, which include discomfort and airway drying. 5 …”
Section: Introductionmentioning
confidence: 99%
“…By this mechanism, mucociliary function and secretion clearance is improved [15], as shown in patients with idiopathic bronchiectasis from the reduced percentage of retention of an inhaled tracer before and after receiving warm and humidified air through NHF [16]. Furthermore, the required metabolic cost of warming and increasing the relative humidity of inspired gas is reduced, especially in patients with increased minute ventilation [17].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%